BREAST CANCER IN UKRAINE DURING THE LAST DECADE - Vynnychenko, O.I.; Lakhtaryna, R.Y.; Moskalenko, Y.V. (World of Medicine and Biology, 2024)
Breast cancer occupies the second place in the structure of morbidity and the fourth place in the structure of mortality among all cancer types. To study the epidemiology of breast cancer, we used data from the National Cancer Registry of Ukraine and the Global Cancer Observatory. From 2014 to 2019, morbidity and mortality rates in Ukraine and the Sumy region were stable. Since 2020, there has been a significant deviation in incidence rates and a rapid decrease in mortality from breast cancer. The most significant decrease in incidence was observed in 2020 and 2022. In 2023, this trend continued. In comparison with Ukraine, the morbidity in the USA is more than twice as high, but the mortality rates are almost the same. In China, the incidence of breast cancer is lower than in Ukraine, but it tends to increase. The decrease in morbidity and mortality in Ukraine cannot be considered an improvement in the epidemiological situation. It is almost impossible to establish accurate data during the war.
Keywords: breast cancer; morbidity; mortality; Ukraine; Sumy region